1947
DOI: 10.1084/jem.85.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Serological Sequences in Experimental Hypersensitivity

Abstract: The histological and serological changes in animals made experimentally hypersensitive to foreign proteins have been separately studied by many investigators. It does not fall within the scope of this report to review the extensive literature dealing with these subjects. It is our purpose to attempt to correlate the sequences in the development of definite tissue changes with concomitant serological studies of the levels of antigen and antibody. The demonstration by Rich and Gregory (1), that a single large in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
1

Year Published

1948
1948
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(30 citation statements)
references
References 15 publications
3
26
1
Order By: Relevance
“…Most attempts to produce experimental animal nephritis by immunological models have centered chiefly on the production of nephritis by single or repeated intravenous injections of foreign protein (15)(16)(17), antigen-antibody complexes (18), or anti-kidney antibodies (13). Heteronephrotoxic sera have been considered to be highly species specific (19,20), but Steblay and Lepper (21) have shown that rabbit antihuman glomerular basement membrane serum will produce nephritis in dogs.…”
mentioning
confidence: 99%
“…Most attempts to produce experimental animal nephritis by immunological models have centered chiefly on the production of nephritis by single or repeated intravenous injections of foreign protein (15)(16)(17), antigen-antibody complexes (18), or anti-kidney antibodies (13). Heteronephrotoxic sera have been considered to be highly species specific (19,20), but Steblay and Lepper (21) have shown that rabbit antihuman glomerular basement membrane serum will produce nephritis in dogs.…”
mentioning
confidence: 99%
“…These are not distinguishable histologically from lesions induced by soluble antigen-antibody complexes [4], Both the fluorescent antibody studies on the renal biopsy tissue and the serial plasma immunoglobulin estimations, serum plasma and complement estimations are in favour of complex disease. There is some evidence that the molecular size of immune complexes determines the site of their deposition in the vascular tree [2,6]. In the kidneys the heavier immune complexes are more likely to be deposited in the glomeruli whereas the lighter complexes will be deposited in the arterial walls.…”
Section: Discussionmentioning
confidence: 99%
“…Hawn and Janeway (17) made similar studies in rabbits using purified preparations of bovine serum albumin and bovine gamma globulin instead of crude serum which contains a mixture of many different proteins. These two chemically and immunologically different serum protein antigens produced quite different reactions.…”
Section: Pathologymentioning
confidence: 99%